Solving security issues in IoT systems - Kolomatska D. S. (НТУ "ДП", 2024)
IoT is a network concept that plays one of the key roles in today's technological environment, providing the ability to connect devices, allowing the exchange of data. Thanks to artificial intelligence and pre-programmed decisions, machines can make autonomous decisions without human intervention. This feature helps improve performance and reduce event response time. An example is the "Smart House" figure 1. "Smart House", like all other Internet IoT things, greatly simplifies human life. For example, having a house with this function, we can program the air temperature, turning on the light, turning on the kettle while being far from the house.
Keywords: системи IoT; мережева концепція; штучний інтелект